An Evaluation of the Role of Field Training Supervisors in the Faculty of Sports Sciences in the Development of the Competencies of the Student Teacher - Al Qarra, Salem; Diabat, Khalaf waleed; Ali, Lina; mazahreh, Jad (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to evaluate the main roles of field training coaches in developing the competencies of student teacher in the Faculty of Sports Sciences. Methods: To achieve its objectives, the study was conducted based on practical and description methods in order to fit the nature of the study. The study sample consisted of college students who were enrolled in the Field Training Course in the Faculty of Sports Sciences at the University of Jordan with a total number of 78 student. A questionnaire was also designed to be used as a compatible tool with current goals of the study. The questionnaire comprised 21categories divided into three sections: planning, executing and evaluating. Results: The study results showed that the role played by field training supervisors in developing the competencies of student teacher, from students’ perspective, was average in both planning and evaluating sections, and it was considerably high in executing. The study also showed no statistical difference in the results among male and female students or students belonging to both public and private schools pertaining to roles affiliated with the field training supervisors in the Faculty of Sports Sciences in developing the competencies of student teacher from students’ perspective. Conclusions: The study recommends holding workshops, lectures and hosting experts in educational supervision to provide students with the necessary and needed knowledge and experiences.